Judith Butler, Race and Education - Chadderton, Charlotte (Springer International Publishing, 2018)
This book provides an analysis of race and education through the lens of the work of Judith Butler. Although Butler tends to be best known in the field of education for her work on gender and sexuality, her work more broadly encompasses the functioning of power and hegemonic norms and the formation of subjects, and thus can also be applied to analyse issues of race. Applying a Butlerian framework to race allows us to question its ontological status, while considering it a hegemonic norm and a performative notion which has a significant impact on real lives. The author considers the implications of Butler's thinking for debates; addressing diverse contemporary educational issues in which race continues to be (re)produced, such as the formation of leaner identities, the production of the good citizen, raising student aspirations, counter terrorism and surveillance in education, and qualitative research in education. This book will be of interest to students and scholars of education and race, the sociology of education and equality of opportunity.